Functional interaction between presynaptic nicotinic and adenosine receptors in the control of dopamine release in the striatum - Garção, Pedro (2013)
Tese de doutoramento do Programa de Doutoramento em Ciências da Saúde, no ramo de Ciências Biomédicas, apresentada à Faculdade de Medicina da Universidade de Coimbra